INFLUENCE FEAR OF MISSING OUT (FOMO) AND QUALITY PRODUCT ON PURCHASING DECISIONS CLOTHES THRIFT THROUGH IMPULSE BUYING IN GENERATION Z IN PALU CITY - Dewa Ayu Diah Resty; Elimawaty Rombe; Muzakir (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine and analyze the influence of Fear of Missing Out (FoMO) and Product Quality on thrift clothing purchasing decisions through Impulse Buying on Generation Z in Palu City. The type of research used is causal associative. The sampling technique in this study uses a purposive sampling method . The sample used was 140 respondents. The data collection technique used was distributing questionnaires and processed using SmartPLS version 4.1. The scale used in this study was a Likert scale and the analysis tool used was PLS. The results showed that the influence of FoMO directly had a positive effect on impulse buying and a negative effect on purchasing decisions, product quality directly had a positive effect on impulse buying and purchasing decisions, and impulse buying had a positive effect on purchasing decisions. The results indirectly show that impulse buying can mediate a strong relationship between FoMO, product quality and consumer purchasing decisions.